UNDERSTANDING THE GENRE FEATURES OF QUALITATIVE RESEARCH: A CASE STUDY - Yi-Huey Guo (Universitas Islam Sumatera Utara (UISU), 2019)
Some researchers’ prejudiced attitude on qualitative research as non-scientific research seems to hinder the development of qualitative research in some Asian social science research communities. Nevertheless, the present study on a qualitative novice’s writing process found that the lowly formulaic style of qualitative research writing could be another reason that impedes such development as well. Novice researchers’ writing tends to follow model-imitation, which contradicts the lowly formulaic style of qualitative research writing. With the employment of a social approach on writing studies as the theoretical framework, this study treated academic writing as an activity influenced by the writer’s situated research community. The writer’s varied research attempts in thesis writing process such as the formulation of research questions, employment of research methods, interpretation of research results, and the like, were treated as his/her composing acts. By longitudinally observing one graduate student’s use of qualitative research in his thesis proposal writing process, the present study discussed the multifaceted nature of qualitative research and the need of teaching/learning qualitative research as a specific genre in academic writing. Related genre elements to be included in teaching qualitative research are addressed.